舌下腺原発扁平上皮癌の1例 - 河原, 康; 石井, 興; 渡邉, 裕之; 釜本, 宗史; 神谷, 祐司; 長縄, 憲亮 (日本口腔外科学会雑誌, 2010)
We report on a 65-year-old woman with primary squamous cell carcinoma of the sublingual gland. She consulted our department because of a painless mass of the left side of the oral floor. The results of a biopsy were squamous cell carcinoma or mucoepidermoid carcinoma. The tentative diagnosis was a malignant tumor of the left sublingual gland. Radical neck dissection, tumorectomy, and reconstruction were performed. Histopathological examination suggested squamous cell carcinoma. Systemic investigation revealed no tumors of other organs; the possibility of a metastatic tumor was ruled out.Because the tumor was localized in the sublingual gland, the diagnosis was primary squamous cell carcinoma of the sublingual gland. This type of carcinoma is rare. To date, the course has been favorable. However, squamous cell carcinoma of the salivary gland has a poor prognosis; follow-up should be continued in the future.